Analyzing the Impact of Environmental Factors on Infectious Disease Transmission in Public Health - Mansour Alhassan Alkhairat, Nawaf Sultan Najmi, Turki Mohammed Shar, Hamad Fahad Alraseeni, Sultanah Refaei ALajmi, Khaled Ahmed Alqahtani (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Many environmental factors influence the dynamics of infectious disease transmission, which presents a serious threat to world health. Effective public health interventions require an understanding of the connection between environmental factors and illness transmission. Methods: The literature on how environmental factors affect the spread of infectious diseases is analysed using a thorough methodology in this review. Using predetermined search terms linked to environmental factors and disease transmission, databases like PubMed, Web of Science, and Scopus were methodically searched. The analysis comprised review papers, research reports, and peer-reviewed articles